Computer security basics - Lehtinen, Rick (O'Reilly, 2006)
This is the must-have book for a must-know field. Today, general security knowledge is mandatory, and, if you who need to understand the fundamentals, Computer Security Basics 2nd Edition is the book to consult. The new edition builds on the well-established principles developed in the original edition and thoroughly updates that core knowledge. For anyone involved with computer security, including security administrators, system administrators, developers, and IT managers, Computer Security Basics 2nd Edition offers a clear overview of the security concepts you need to know, including access controls, malicious software, security policy, cryptography, biometrics, as well as government regulations and standards. This handbook describes complicated concepts such as trusted systems, encryption, and mandatory access control in simple terms. It tells you what you need to know to understand the basics of computer security, and it will help you persuade your employees to practice safe computing. Topics include: Computer security concepts Security breaches, such as viruses and other malicious programs Access controls Security policy Web attacks Communications and network security Encryption Physical security and biometrics Wireless network security Computer security and requirements of the Orange Book OSI Model and TEMPEST.